Infected Vulvar Epidermoid Cyst Mimicking Bartholin and Perianal Pathology in a Young Woman: A Case Report - J, Dr Manaswini; E, Dr Shanthi (International Journal of Aquatic Research and Environmental Studies, 2026)
Background- Vulvar cystic lesions constitute a heterogeneous group of benign conditions that can pose diagnostic challenges in gynaecologic practice. Although Bartholin duct cysts and abscesses are the most common causes of unilateral labial swelling in reproductive-age women, other entities, such as epidermoid cysts, must be considered, particularly when clinical and imaging findings are atypical. Epidermoid cysts are benign, keratin-filled lesions that are relatively uncommon in the vulvar region and may clinically mimic Bartholin or perianal pathology. Case Presentation- A 21-year-old unmarried woman presented with a progressively enlarging, painful swelling of the left labia majora of one month duration. Clinical examination revealed a tense, mobile cystic mass measuring approximately 5 × 6 cm without erythema or discharge. Ultrasonography suggested a chronic perianal abscess with labial extension. Magnetic resonance imaging demonstrated a welldefined heterogeneous cystic lesion with diffusion restriction in the left posterolateral vulvar region. Surgical excision was performed, and intraoperatively, thick keratinous material was evacuated following cyst rupture. Histopathological examination confirmed the diagnosis of an infected epidermoid cyst. The postoperative course was uneventful. Conclusion- Vulvar epidermoid cysts, though uncommon, should be included in the differential diagnosis of unilateral labial swellings. Imaging findings may mimic an abscess, and definitive diagnosis relies on histopathological confirmation. Complete surgical excision provides excellent outcomes and prevents recurrence.